Thomas Aquinas on faith, hope, and love : edited and explained for everyone - Kaczor, Christopher, 1969- (Catholic University of America Press, 2020)
Thomas Aquinas on faith, hope, and love provides essential passages from Thomas's treatment of the theological virtues in the Summa theologiae, edited and explained for classroom use or the independent reader.